The effect of centred versus offset interpenetration on C2H2 sorption in hybrid ultramicroporous materials. Issue 84 (9th October 2017) - Bajpai, Alankriti; O'Nolan, Daniel; Madden, David G.; Chen, Kai-Jie; Pham, Tony; Kumar, Amrit; Lusi, Matteo; Perry, John J.; Space, Brian; Zaworotko, Michael J.
Abstract : Fine-tuning of hybrid ultramicroporous materials (HUMs) can significantly impact their gas sorption performance. Abstract : Fine-tuning of hybrid ultramicroporous materials (HUMs) can significantly impact their gas sorption performance. This study reveals that offset interpenetration can be antagonistic with respect to C2 H2 separation from C2 H2 /C2 H4 gas mixtures.